2000
DOI: 10.1016/s0960-9822(00)00833-2
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans is a model host for Salmonella typhimurium

Abstract: The idea of using simple, genetically tractable host organisms to study the virulence mechanisms of pathogens dates back at least to the work of Darmon and Depraitère [1]. They proposed using the predatory amoeba Dictyostelium discoideum as a model host, an approach that has proved to be valid in the case of the intracellular pathogen Legionella pneumophila [2]. Research from the Ausubel laboratory has clearly established the nematode Caenorhabditis elegans as an attractive model host for the study of Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
232
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(247 citation statements)
references
References 22 publications
7
232
0
8
Order By: Relevance
“…Salmonella typhimurium, Serratia marcescens, and Burkholderia pseudomallei, kill the nematode Caenorhabditis elegans when supplied as a food source, and a variety of bacterial virulence factors have been shown to play a role in both nematode and mammalian pathogenesis (1)(2)(3)(4)(5)(6). In addition, C. elegans mutants that are either more susceptible or more resistant to bacterial killing can be readily identified (7,8).…”
Section: S Everal Human Pathogens Including Pseudomonas Aeruginosamentioning
confidence: 99%
“…Salmonella typhimurium, Serratia marcescens, and Burkholderia pseudomallei, kill the nematode Caenorhabditis elegans when supplied as a food source, and a variety of bacterial virulence factors have been shown to play a role in both nematode and mammalian pathogenesis (1)(2)(3)(4)(5)(6). In addition, C. elegans mutants that are either more susceptible or more resistant to bacterial killing can be readily identified (7,8).…”
Section: S Everal Human Pathogens Including Pseudomonas Aeruginosamentioning
confidence: 99%
“…In contrast, relatively little is known about innate immunity in the nematode Caenorhabditis elegans. Recent work has shown that C. elegans is killed by a variety of bacterial and fungal pathogens, including Pseudomonas aeruginosa (4)(5)(6)(7)(8)(9)(10)(11)(12). When this experimental host-pathogen system was used, a forward genetic screen for C. elegans mutants exhibiting enhanced susceptibility to P. aeruginosa-mediated killing (Esp phenotype) identified two components of a mitogen-activated protein kinase (MAPK) signaling cascade, the MAPK kinase kinase, NSY-1, and the MAPK kinase, SEK-1, that are required for pathogen resistance (13).…”
mentioning
confidence: 99%
“…Some bacterial pathogens, such as Salmonella enterica serovar Typhimurium are able to establish a persistent infection in the intestine of C. elegans, reducing the life span of the host. Several genes needed for virulence in mammals are also required for pathogenesis in C. elegans (2,10,16,28), implying that the invasion and proliferation of serovar Typhimurium in the host intestine depend on mechanisms common to the nematode and mammals. This makes C. elegans a relevant model for determining the infectivity and fitness of antibiotic-resistant bacteria during a host infection.…”
mentioning
confidence: 99%
“…Although mouse models have been used for these purposes, simpler invertebrates such as Caenorhabditis elegans have recently become more attractive for assessing the in vivo biological costs of antibiotic resistance (23,24). Many bacterial genes known to be required for mammalian pathogenesis are needed also in the nematode (1,9,11,15,16,27,28). Some bacterial pathogens, such as Salmonella enterica serovar Typhimurium are able to establish a persistent infection in the intestine of C. elegans, reducing the life span of the host.…”
mentioning
confidence: 99%
See 1 more Smart Citation